Cancer Diagnosis and Mental Health among Older White Adults: Moderating Role for Social Networks?. (November 2015) - Schafer, Markus H.; Koltai, Jonathan
Cancer is a life-changing condition for many American seniors, and a growing body of literature is assessing the mental health implications of living with the disease. This article builds from the well-known buffering hypothesis with insights from recent cancer research to investigate whether social networks moderate the association between cancer and mental health for older men and women. Analyses use two waves of survey data (2005-2006 and 2011) from the National Social Life, Health, and Aging Project (N = 1, 367), enabling us to track new diagnoses of cancer and network dynamics over time. Consistent with a stress-buffering pattern, larger and growing networks were associated with lower rates of depressive symptomology among women survivors relative to those with small and shrinking networks. There was little evidence that emotional closeness to network members or density moderated the mental health consequences of cancer among men or women.